Dynamic spectral study of Pc 3 to Pc 5 pulsations observed near L=6 - Tonegawa, Yutaka; Fukunishi, Hiroshi; Hirasawa, Takeo; McPherron, Robert L.; Sakurai, Tohru; Kato, Yoshio (1983)
P(論文) Dynamic spectral characteristics of magnetic pulsations in the frequency range from Pc3 to Pc5 are examined on the basis of the magnetic field data observed at the synchronous orbit, ATS 6 and at the high latitude ground stations, Syowa (L∿6) and Mizuho (L∿7) in Antarctica, and Husafell (a conjugate station to Syowa) in Iceland. The dynamic spectral power seen at both locations shows generally a similar frequency structure throughout the daylight hours. It contains several dominant frequency trends consisted of a harmonic relation with one another. The satellite location with respect to the magnetic latitude along the field line is very sensitive to the spectral structures seen in the dynamic spectra. When the satellite was located 10°above the magnetic equator, the spectra appeared with two dominant spectral trends. One of them was the lowest frequency trend corresponding to the Pc 4-5 frequency range (3-10mHz) and another trend was seen in the Pc3 frequency range (20-80mHz). They exhibited a harmonic relation with each other. When the satellite was located near the magnetic equator, the lowest frequency trend did not appear and its second harmonics became visible. In the dynamic spectra of the ground station, the spectral trends in the Pc3 and Pc4-5 are also in a harmonic relation with each other, seen similarly at the satellite location only except for many dotted structures with an interval of a few tens of minutes. departmental bulletin paper